2018
DOI: 10.1177/0300060518775585
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnosis consumption of preserved vegetables and prognosis of invasive oesophageal squamous cell carcinoma: a prospective cohort study in one high-risk area in China

Abstract: ObjectiveTo investigate the prognostic effect of pre-diagnosis preserved vegetable consumption on oesophageal squamous cell carcinoma (ESCC) in Yanting County, China.MethodsThis prospective cohort study enrolled consecutive patients with ESCC. The pre-diagnosis diet consumption data were collected using a food frequency questionnaire at baseline. Preserved vegetable consumption was categorized into two groups: < 1/week and ≥1/week. Kaplan–Meier survival curve analysis with a log-rank test and a Cox proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…There was no association between prediagnosis green vegetable intake and overall mortality in pancreatic cancer patients ( 42 ). A Chinese study reported that the higher consumption of fermented preserved vegetables before diagnosis significantly correlated with a higher risk of all-cause mortality in esophagus cancer patients ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There was no association between prediagnosis green vegetable intake and overall mortality in pancreatic cancer patients ( 42 ). A Chinese study reported that the higher consumption of fermented preserved vegetables before diagnosis significantly correlated with a higher risk of all-cause mortality in esophagus cancer patients ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…The main cause for this classification was the concern of changes in exposure status among patients. In addition, minor reasons reducing the quality of studies were observed: bias due to confounding ( 40 , 41 , 57 ), bias in classification of exposures ( 39 , 40 , 42 , 47 , 48 , 56 ), and bias in selection of the reported results ( 36 , 39 , 41 , 42 , 57 , 61 ) ( Supplemental Table 7 ). More details about the items considered in both the ROBINS-E and the STROBE-nut scale are provided as supplementary material ( Supplemental Tables 8 and 9 , respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of 4215 duplicates, 3795 potentially eligible records were left, of which 3677 were excluded after reviewing the titles and abstracts. Finally, 15 eligible cohort studies [12][13][14][15][23][24][25][26][27][28][29][30][31][32][33] containing 6826 esophageal cancer patients were identified through full text review of 118 studies. The most common reasons for exclusion were study designs, lack of data on dietary exposure and no outcomes of interest.…”
Section: Literature Retrievalmentioning
confidence: 99%